NASHR AL-ʿILM AND THE WIDENING GROUNDS OF PUBLIC LEGITIMACY IN EARLY ISLAMIC SOCIETY - Maulidatuzzakiyah; Tiara Wardatutsaniyah; Muhammad Suyudi; Syamsudin (UIN Syarif Hidayatullah Jakarta, 2026)
This article examines the ḥadīth of Kitmān al-ʿIlm as a normative foundation for the ethics of Nashr al-ʿIlm and its relation to public legitimacy in early Islamic society, understood here as the socially intelligible grounds through which public responsibility could be justified, recognized, or accepted. Existing studies of educational ḥadīth often approach ḥadīth reports as sources of pedagogical values, while the connection between the ethics of knowledge transmission, social recognition, and public responsibility remains less fully explored. This interpretive literature-based study employs a textual-contextual reading of reports recorded by Abū Dāwūd, al-Tirmidhī, Ibn Mājah, al-Bukhārī, and Muslim, supported by classical discussions of adab al-ʿilm, early Islamic historiography, and relevant modern scholarship. The analysis distinguishes textual findings, historical observations, and conceptual synthesis. The findings show that the prohibition against concealing knowledge does not require unrestricted disclosure. Rather, it rejects the arbitrary withholding of needed knowledge when its transmission is required. Historical traces associated with Dār al-Arqam, the teaching of the Qurʾān in Yathrib, Ahl al-Ṣuffah, and the dispatch of Companions function as contextual indications, not as direct proof of social transformation. The reports concerning Usāmah ibn Zayd and Ibn Abzā are treated as illustrative cases in which recognized personal or scholarly capacity could enter the evaluation of public responsibility without erasing lineage, seniority, or social designation. The term “epistemic meritocracy” is used only as a limited analytical marker for this evaluative process. The article contributes to Qur’an and Ḥadīth Studies by expanding educational ḥadīth analysis beyond direct pedagogical application toward the ethical and social conditions through which knowledge becomes transmissible, recognizable, and publicly meaningful.